Immunization status lowers the incidence of stunting in children 1-5 years - Gracia Natalia Theresia; Verawati Sudarma (World Nutrition Journal, 2022)
Stunting is a multifactorial condition where a toddler has less body length compared to their age. One of the factors is the immunization status of children, which can lead to susceptibility to infection and caused growth disturbance. This study was conducted to determine whether immunization plays a role as one of the interventions to prevent stunting in children age 1-5 years by using cross-sectional observational study with a total of 110 children aged 1-5 years who visited the Public Health Center of Jatinegara District, East Jakarta between September-November 2019. Questionnaires, anthropometric assessment using body length board and microtoice, and Z-score assessment were obtained during the study. The Chi-square test was performed for data analysis. The result of this study showed that 47,3% of respondents had incomplete immunization status, and 84.6% of child were stunted. Immunization plays a role as one of the factors preventing stunting in children age 1-5 years (p<0,001). It can be concluded that immunization is one of the factors contributing to lowered incidence of stunting in children age 1-5 years.